Needs Analysis of Creating an Android-Based for Istimā‘ Learning Materials - Ihwan Rahman Bahtiar (Al-Ma‘rifah, 2020)
The growing users of Android-based devices among students and demands the implementation of online learning to encourage innovation in the preparation of learning. One of the innovations following these conditions is the preparation of teaching materials based on Android. The purpose of this study is to find out of needs analysis of Android-Based learning materials for istimāʻ (lisetening) III in Arabic Language Education Study Program, Faculty of Languages and Arts, Universitas Negeri Jakarta. The study analyses the student needs using the descriptive method. While the data will be collected questionnaire. Then, the data analyzed with a quantitative technique. There are three steps of the process that will go through, namely data reduction, data display, and taking a conclusion. The sample of this study was 40 fifth semester students. The result of the study shows that all students own and use based on Android smartphones and students want istimāʻ III materials to build in the based-on Android application.